건강신념모델을 적용한 치과위생사의 손씻기 수행 관련요인 분석 - 임미희; Mi Hee Lim (Han'guk Ch'iwisaeng Hakhoe chi, 2013)
Objectives : The purpose of this study was to examine influential factors related to hand washing practice in dental hygienists by health belief model, one of the major predictors of health behavior including perceived susceptibility, perceived seriousness, perceived benefits, perceived barriers and cues to action. Methods: The subjects were dental hygienists in dental hospitals, dental clinics, general hospitals and university hospitals in Seoul. A survey was conducted from May 1 to September 30, 2011. Results: Analysis of health belief of dental hygienists in hand washing, they revealed the highest marks of 4.39 to perceived benefits, followed by perceived susceptibility(4.29), perceived seriousness(3.94), cues to action(3.30) and perceived barriers(1.81). The mean was 4.13 in hand washing practice. The senior and well educated dental hygienists in general hospitals had a tendency to wash hands frequently. It is statistically significant(p<0.05). In regard to the correlation among the subfactors of health beliefs, susceptibility had a statistically significant positive correlation to seriousness, benefits and cues to action, and seriousness was positively correlated to benefits and cues to action. Conclusions: It is necessary to develop and implement hand washing education program for dental hygienists focusing on perceived benefits and barriers which are two of the health beliefs affecting the hand washing practice.